IN-VITRO EVALUATION OF PHYTOCHEMICALS, HEAVY METALS AND ANTIMICROBIAL ACTIVITIES OF LEAF, STEM AND ROOTS EXTRACTS OF CALTHA PALUSTRIS VAR. ALBA - Syed Wajid Ali Shah; Muhammad Siddique Afridi; Mujaddad Ur Rehman; Azam Hayat; Abid Sarwar; Tariq Aziz; Metab Alharbi; Abdulrahman Alshammari (Journal of the Chilean Chemical Society, 2023)
Plants are a rich source of secondary metabolites that have been found to have medicinal properties. The present study was conducted to evaluate the phytochemical screening, antimicrobial activities, and heavy metal analysis in different parts (leaves, stem and roots) of Caltha palustris var. alba. The phytochemical analysis for the plant was carried out in ethanol, acetone, ethyl acetate, n-hexane and deionized water extracts. The phytochemical screening confirmed the presence of several bioactive compounds like, alkaloids, flavonoids, tannin, phenols, and saponin. The antimicrobial activity was determined by the agar disc diffusion method using five different extracts. The antimicrobial study revealed that the C. palustris var. alba has the ability to fight against the selected microorganism. The phytochemical and biological screenings were correlated with the presence of heavy metals in selected plant C. palustris var. alba. The concentrations of heavy metals were determined by atomic absorption spectrophotometer and revealed the presence of the metals like cadmium, manganese, zinc, copper, lead, and chromium. The metal concentration was compared with the permissible limit set by World Health Organization (WHO) and the result was discussed. From these studies, it is clear that plant C. palustris var. alba can be used for medicinal purposes.